Decision-making in selected public school elementary schools an emergent model - Impuesto, Rose Bolante (2006)
The study aimed to develop a model of Filipino school administrator's decision-making to help in understanding how Filipino administrators make decisions. The study was conducted in the school divisions of Pasig City San Juan, and Marikina City. Fifty public elementary school principals served as the respondents of this qualitative and quantitative research. Among the important findings are: that school administrators often use decision-making processes in solving problems, that some of the problems that influence their decisions include those related to students, organization and faculty, parents and the community, and school facilities and budget, etc. It was recommended that the rational process of decision-making be adopted by school principals in the Division of Pasig City and San Juan and in the Division of Marikina City.